Do Mexicans care about air pollution? - José Iván Rodríguez-Sánchez (Latin American Economic Review, 2014)
Mexico has many major problems such as corruption, poverty, illiteracy, unemployment, pollution, etc. Regarding pollution, politicians have established some programs trying to improve air quality in Mexico. But they do not know if Mexicans care about air pollution or they prefer that government faces other problems. This paper answers this question and in fact, we conclude that Mexicans do care about air pollution (measured by Particulate Matter) and they agree to pay to reduce it. This paper follows a residential sorting model to calculate marginal willingness to pay for a reduction in air pollution. Our estimates imply that the household head in Mexico would pay 443.66 to 2,682.92 (in constant 2000 Mexican pesos) or 46.90-283.61 (2000 dollars) for a one-unit reduction in Particulate Matter emissions per year. Therefore, there are benefits to reduce this problem in Mexico and the government and private firms must face this problem since the costs are lower than those benefits.
Keywords: D1; Q2; Q5; R1; 330; Particulate matter; Migration costs; Discrete choice models; Valuation of air quality in Mexico